Fuzzy controller design for multivariable systems - Guo, Aiwei (2014)
Dehumidification has been widely used both in industry as well as in household. There are many dehumidification methods, among which liquid-desiccant dehumidification is proved to be very efficient with less energy consumption. The whole liquid-desiccant dehumidification and air-conditioning system comprises of Dehumidification unit, Regeneration unit and Heat Exchanger Unit. Liquid-desiccant dehumidification removes the moisture of the outer air by utilizing the difference of the water concentration between the air and the solution; the regeneration unit, in contrast, regenerates the diluted solution to an acceptable higher concentration so that it can be used later; thus maintaining a continual operation cycle. Fuzzy